De trinitate Nowacjana wobec herezji patrypasjanizmu - Sordyl, Krzysztof (Vox Patrum, 2008)
The paper is an analysis of Patripassianism using a historico-exegetical approach, with a special consideration given to Novatian’s tractate, De Trinitate. The Roman theologian differs considerably in his account of the Patripassian heresy from his two great predecessors, Hippolytus and Tertullian. The two authors’ discussion is often heated, with a very distinct, polemical tonę. In contrast, Novatian offers hardly any historical data. He only mentions Sabellius twice. The polemical tonę is morę moderate, the discussion less involved. A certain tracę of his critiąue of Patripassianism can be found in Novatian’s theology of the Logos. He does not organise his arguments according to divine economy or the notion of dispositio - which he knows and he uses. The Roman author presents Patripassianism in the following three chapters of his work: 26-28. Moreover, certain aspects of this teaching may be found in his discussion with ditheism, in chapters 30-31. According to Novatian, Patripassianism is a way of identifying the Father with the Son, which is done on the pretext of defending orthodox monotheism. The Roman theologian uses that as a key in his understanding, at the same time refuting charges of ditheism or negating the distinctiveness of the Son. His discussion with Patripassianism is mainly exegetical in nature. He shows the distinction that exists between the Father and the Son. He also refutes his opponents’ arguments that are based on their exegesis of the two Scriptures, John 10:30 and John 14:9. However, he does not discuss the problem of understanding theofany by Patripassians. In De Trinitate 12, 65 Novatian addresses the adherents of Filiopaterism, attempting to demonstrate their false argumentation. A careful analysis of this text leads to the conclusion that the polemic in this chapter of the tractate does not only apply to Filiopaterism but also to those who hesitate between Adoptianism and Patripassianism. In De Trinitate 24, 136 Novatian offers an exegesis of Lukę 1:35. In this exegesis he argues against Adoptianists, also including filiopaterism of Calixtus. There is no fully Patripassian exegesis in any point of Novatian’s argumentation. The Roman theologian also discusses relations between Adoptianism and Patripassianism. In both heresies he finds traces of Jewish influences, especially in the subject of antitriniatarian monotheism. A separate character of the heresy of Adoptianism and Patripassianism seems to be obvious to him. A bridge between them may be found in Filiopaterism, which is a blend of Adoptianism and Patripassianism in order to preserve radical monotheism. Novatian knew this position through his lecture of Against Praxeas and Refutatio.